2022
DOI: 10.1186/s12903-022-02682-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of M2 macrophage-derived exosomes facilitating osteogenic differentiation of human periodontal ligament stem cells

Abstract: Background The role of periodontal ligament stem cells (PDLSCs) and macrophage polarization in periodontal tissue regeneration and bone remodeling during orthodontic tooth movement (OTM) has been well documented. Nevertheless, the interactions between macrophages and PDLSCs in OTM remain to be investigated. Consequently, the present study was proposed to explore the effect of different polarization states of macrophages on the osteogenic differentiation of PDLSCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Moreover, M2-exos play an important role in bone formation and resorption balance. Previous studies have shown that M2-exos increase pro-inflammatory cytokines and suppress osteoblast differentiation of bone marrow mesenchymal stem cells and PDLSCs [ 27 , 28 ]. In addition, Chen et al [ 29 ] have reported that M2-exos impede bone marrow-derived macrophage osteoclast formation via the IL-10/IL-10R pathway, thereby reducing alveolar bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, M2-exos play an important role in bone formation and resorption balance. Previous studies have shown that M2-exos increase pro-inflammatory cytokines and suppress osteoblast differentiation of bone marrow mesenchymal stem cells and PDLSCs [ 27 , 28 ]. In addition, Chen et al [ 29 ] have reported that M2-exos impede bone marrow-derived macrophage osteoclast formation via the IL-10/IL-10R pathway, thereby reducing alveolar bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high permeability, low clearance, non-toxicity, therapeutic functions and the application of drug carriers, exosomes were widely studied for tissue regeneration [ 14 ]. Similar to M2 macrophages, M2-EXO was well-documented in inflammation targeting and elimination, angiogenesis, tumor growth, and bone formation [ 17 , [27] , [28] , [29] ]. However, its role in periodontal regeneration was rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies confirmed that M2-EVs could promote the osteogenesis of BMMSCs by delivering multiple miRNAs, such as miR-690 , miR-5106 and miR-26a-5p [ 80 , 82 , 83 ]. In terms of periodontal bone regeneration, Liao et al pointed out that M2-EVs might also promote the osteogenic differentiation of PDLSCs through a variety of miRNAs [ 84 ]. In addition to miRNAs, Chen et al found that M2-EVs were rich in IL-10, which promoted BMMSC osteogenic differentiation through IL-10/IL-10R signaling pathway, inhibited osteoclast formation, and reduced bone resorption in mice with periodontitis [ 56 ].…”
Section: Cevs and Periodontal Regenerationmentioning
confidence: 99%